1998
DOI: 10.1007/s002340050623
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord abscess in a heroin addict: case report

Abstract: Spinal cord abscesses are extremely rare, even in intravenous drug abusers. They usually have a poor prognosis unless diagnosed and treated promptly. MRI is the best imaging modality for diagnosis and follow-up. We report a 42-year-old man, an active intravenous drug user, HIV negative, who developed subacute tetraplegia from an intramedullary abscess caused by Staphylococcus aureus. Immediate decompressive surgery and antibiotic treatment led to progressive recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…HIV infection, prolonged steroid therapy and drug addiction also seem to play a signi®cant role. 14,19,23 Our patient was neither in an immunocompromised state nor was there any evidence of primary infective focus.…”
Section: Managementmentioning
confidence: 73%
See 1 more Smart Citation
“…HIV infection, prolonged steroid therapy and drug addiction also seem to play a signi®cant role. 14,19,23 Our patient was neither in an immunocompromised state nor was there any evidence of primary infective focus.…”
Section: Managementmentioning
confidence: 73%
“…The veins in the vicinity are frequently thrombosed. 14 The infective foci commonly seen are pneumonitis, genitourinary tract infection, peripheral skin infections, endocarditis and meningitis. 15,23 Abscesses are also associated with dermoids, 29 epidermoids, 22 infected dermal sinus tract, 30 ± 32 ependymomas 33 and spinal dysraphism.…”
Section: Managementmentioning
confidence: 99%
“…Twenty-five patients with ISCA were identified in addition to the present patient, 18 males and 8 females aged 1 month to 74 years (mean 32 years). 1,5,[8][9][10][11][12]14,16,20,[23][24][25][26][27][29][30][31][32][33][34][35][36] No significant difference was found in mean age between women and men (22 years vs. 36 years; p = 0.16), but women tended to be affected in the first five decades, whereas men were affected mainly in the first and sixth decades (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Abuse of intravenous drugs has been associated with a higher prevalence of spinal abscess due, in part, to hematogenous spread of bacteria from contaminated syringes and needles . Several studies have documented primary pyogenic infection of the spine in intravenous drug users , and several case studies have reported spinal abscess in patients who are heroin addicts .…”
Section: Introductionmentioning
confidence: 99%